Preparation of NiPt Alloys by Galvanic Replacement Reaction on Ni Films for Direct Ethanol Fuel Cell - Vinh, Pham Van (Communications in Physics, 2017)
NiPt alloys were prepared successfully by galvanic replacement reaction on the surface of Ni films. The electrolytic deposition of Ni films was investigated to get the high qualities of Ni films for the galvanic reaction. The influence of the electrolytic currents on the morphology and thickness of Ni films were observed by SEM. The thickness and roughness of the Ni films increase with the increase of electrolytic currents. XRD patterns showed that Ni films were formed in the crystal phase of Ni corresponding to face centered cubic structure. Pure Ni films obtained by annealing the films in hydrogen medium were used to prepare NiPt alloys due to galvanic reaction of Pt2+ with Ni2+ in H2PtCl6 solution. The influence of the H2PtCl6 solution concentration on the composition of NiPt alloys were investigated by EDX. The analyses results showed that NiPt alloy formed by using high solution concentration of H2PtCl6 has high composition of Pt. The electrocatalytic activities of both Ni films and NiPt alloys toward ethanol oxidation in KOH medium were carried out by the cyclic voltammetry measurement. Alloyed samples exhibited high electrocatalytic activities due to carbonaceous removal and weakening Pt-COads bond